PENGARUH GAYA BELAJAR AUDITORI TERHADAP KINERJA PRAKTIKUM - Muhammad Haikal Kyandaru (CV. ADIBA AISHA AMIRA, 2024)
Learning styles themselves are divided into three areas, namely visual, auditory and kinesthetic learning styles. All students should have these three learning styles. But the fact is that each learner has a different learning style. Auditory learning style itself is a learning style where students use their sense of hearing to capture and understand information, such as by listening to audio tapes, listening to video tutorials, and listening to lecturers' instructions. Auditory learning style has two types of influence on practicum performance, namely positive influence and negative influence. In this article, it is explained that the positive effect of auditory learning style on practicum is that students are able to understand information from the lecturer's instructions only through verbal messages (lectures) without seeing the jobsheet. In addition, there is also a perceived advantage that students are able to multitask during practicum, such as listening to video tutorials at the same time as the practicum process. Meanwhile, the negative effect described in this article is that there will be differences in the speed of understanding ability among students if the teacher only provides instructions through the jobsheet.